Combining supercapacitor and energy harvesting devices with magnets integrated with interfacial materials for efficient current transfer - Choon, Si Lin; Lim, Hong Ngee (American Chemical Society, 2024)
Various photosupercapacitor designs reported are usually integrated with permanently positioned interfacial layers, such as carbon-based materials, conductive ink, and conductive tape that joins the solar cell and supercapacitor. Nonetheless, the uncomplicated and separable photosupercapacitors have not been revealed yet. Herein, an assembled photosupercapacitor combined via magnets that is easily separable into solar cell and supercapacitor components is reported in this study, facilitating component maintenance or replacement whenever a separation is needed. The size of the contact materials between the magnet sheets is optimized based on the optimum magnetic attraction. Graphene nanoplatelets (GNPs) show performance comparable to that of an interfacial material (compared with Cu tape, polypyrrole (Ppy), and Ag ink) between the substrate and the contact material (graphite sheet) compared with the sputtered metals, such as Pt and Au. This assembly, combined with magnets, streamlines the energy conversion processes, showcasing its potential for innovative electronic integration.